Study on temperature fields and influencing factors of point-line meshing gear drive used in low speed and heavy load conditions - MA Ziyong; TIAN Yinghu; LIU Jin; WANG Zilong; YANG Wei (Jixie chuandong)
ObjectiveThe tooth profiles of point and line meshing gears combine the advantages of involute gears’ convex contact and arc gears’ convex contact, which are widely used in hoisting, mining, metallurgy and other low-speed and heavy-duty fields. The lubricating oil film of the gear contact surface is easy to break under heavy load, and the tooth surface will produce instant high temperature and bond, resulting in intensified wear of the tooth surface, reducing the bearing capacity and affecting the service life. Therefore it is crucial to research the temperature field distribution of the low-speed and heavy-duty point line meshing gear drive used in coal mill and its influencing factors.MethodsFirstly, based on the slice method, the Hertzian contact theory and the tribology principle, the calculation formulas of the tooth surface temperature rise and the frictional heat flux were derived. Then, the temperature field of the tooth surface of the point and line meshing gear drive was simulated with a concrete example, the finite element software Ansys (APDL), and the heat generation of each tooth surface and the temperature distribution of the meshing surface were analyzed. Finally, the influence of geometric parameters and working conditions of the point and line meshing gear drive on the temperature field of tooth surface was studied.ResultsThe results show that the highest temperature of the driving wheel with the point-line meshing gear appears in the middle part of the tooth width near the top of the tooth, the highest temperature of the driven wheel appears near the junction of the concave and convex tooth profile, and the temperature of the driving wheel is obviously greater than that of the driven wheel. In addition, increasing the speed of the driving wheel, reducing the displacement coefficient and reducing the transmission power in a certain range can reduce the frictional heat flux of the tooth surface to different degrees, and the temperature field distribution is more uniform. The transmission power has great influence on the temperature field. When the transmission power is reduced from 110 kW to 60 kW, the maximum temperature of the tooth surface is reduced by 27.2%. The research on the temperature field of point and line meshing gear tooth surface and its influencing factors can provide reference for tooth profile modification, noise reduction and life extension of point and line meshing gears.